2011
DOI: 10.1007/s00280-011-1704-y
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter analysis of GTX chemotherapy in patients with locally advanced and metastatic pancreatic adenocarcinoma

Abstract: PurposeStudies treating adenocarcinoma of the pancreas with gemcitabine alone or in combination with a doublet have demonstrated modest improvements in survival. Recent reports have suggested that using the triple-drug regimen FOLFIRINOX can substantially extend survival in patients with metastatic disease. We were interested in determining the clinical benefit of another three-drug regimen of gemcitabine, docetaxel and capecitabine (GTX) in patients with advanced pancreatic adenocarcinoma.Patients and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…A retrospective study of 154 patients with advanced pancreatic cancer treated with GTX reported a response rate of 11% and median survival of 11.6 months (in stage IV patients; ref. 46). The rate of grade 3 or worse hematologic toxicities was 41%.…”
Section: Docetaxel-in the Context Of "Gtx"mentioning
confidence: 88%
“…A retrospective study of 154 patients with advanced pancreatic cancer treated with GTX reported a response rate of 11% and median survival of 11.6 months (in stage IV patients; ref. 46). The rate of grade 3 or worse hematologic toxicities was 41%.…”
Section: Docetaxel-in the Context Of "Gtx"mentioning
confidence: 88%
“…Until recently, the standard of care for metastatic disease had been the nucleoside analogue, gemcitabine [1]. However, this convention has been challenged by recent studies showing significant survival advantage with FOLFIRINOX (5-FU, irinotecan, and oxaliplatin) [2] and other combination chemotherapies [35]. …”
Section: Introductionmentioning
confidence: 99%
“…None of the patients had a radiologic response to treatment. The second retrospective review by De Jesus-Acosta et al included 154 patients treated with GTX in any line of therapy for metastatic disease, with 51% of patients receiving first-line GTX 16. Patients who were chemotherapy-naïve demonstrated a median overall survival of 11.6 months, while those who received it as a second line or greater had a median overall survival of 5.7 months.…”
Section: Introductionmentioning
confidence: 99%